Circulating “Empty” Platelets In Hemolytic Uremic Syndrome And Thrombotic Thrombocytopenic Purpura - Lüchters, G; Budde, U; Klehr, U; Müller, N (Thrombosis and Haemostasis, 1981)
In two patients (1 male, 1 female) the diagnosis of hemolytic uremic syndrome (HUS) and in one male patient the diagnosis of thrombotic thrombocytopenic purpura (TTP) was confirmed. All patients showed a platelet aggregating factor in plasma. PgI2-stimulating activity of patient’s plasma was defective or absent. Platelet count was low and platelet aggregation was severely impaired. Even with high amounts of ADP (20 μM) only first phase aggregation could be seen. Epinephrine induced aggregation was absent. The highest amount of collagen used (20 μg/ml) induced only a small aggregation and no ATP-secretion. Thrombin stimulated ATP-secretion was decreased while Ristocetin induced aggregation was normal. ATP- and ADP-content of platelets was low and ATP/ADP ratio was raised above the normal value. Platelet spreading was severely impaired.From these findings we conclude that at least part of the platelets in these related diseases are circulating “empty” platelets which underwent degranulation in the patient’s blood vessels.